1. Cortical functional correlates of responsiveness to short-lasting preventive intervention with ketogenic diet in migraine: A multimodal evoked potentials study. Issue 12 (December 2016) - Bracaglia, M.; Coppola, G.; Di Lorenzo, C.; Di Lenola, Davide; Serrao, M.; Parisi, V.; Pierelli, F.
Abstract : A ketogenic diet (KD) – a drastic restriction in carbohydrate and lipid intake promoting fat metabolism and ketone body synthesis – has a role in preventing migraine. Here, we aim to identify cortical neurophysiological correlates of responsiveness to short-lasting preventive intervention with KD in migraine. Thus, we recorded visual (VEPs) and median nerve somatosensory (SSEPs) evoked potentials in 18 interictal migraine patients before and after 1 month of KD during ketogenesis. We measured VEP N1-P1 and SSEP N20-P25 amplitudes respectively in 6 and in 2 sequential blocks of 100 sweeps as well as habituation as the slope of the linear regression between block 1 and 6 for VEPs or between 1 and 2 for SSEPs. After 1-month of KD, a significant reduction in the mean attack frequency and duration was observed (all P < 0.001). The KD did not change the 1st SSEP and VEP block of responses, but significantly induced normalization of the interictally reduced VEPs and SSEPs (all p < 0.01) habituation during the subsequent blocks. KD could restore normal EPs habituation curves during stimulus repetition without significantly changing the early amplitude responses. Thus, we hypothesize that KD acts on habituation regulating the balance between excitation and inhibition at the cortical level.